REVITALISASI UPACARA ADAT SEREN TAUN SEBAGAI MEDIA EDUKASI KULTURAL MASYARAKAT CIGUGUR KUNINGAN - Muhammad Gilang Abdya Fachreza; Aris Kurniawan (PT. Hasba Edukasi Mandiri, 2025)
Indonesia is a country rich in culture, influenced by various geographical conditions and a long historical journey, resulting in the formation of various traditions that are still preserved to this day. This research discusses the Seren Taun ceremony tradition in Cigugur, Kuningan, West Java, as one of the cultural traditions of the Sundanese community. Seren Taun has three main values. First, as an expression of gratitude to God for a sufficient harvest, this tradition teaches the importance of gratitude to the God of the universe. Second, Seren Taun serves as a unifying medium for the people of Cigugur who live in religious and belief diversity, fostering relationships among fellow humans. Third, this ceremony plays a role in preserving traditions passed down by previous generations, thereby fostering a love for preserving nature. Seren Taun is not just a ceremonial traditional ritual, but serves as an educational medium to preserve the cultural identity of the Sundanese ancestors.